148k views
5 votes
If you apply the changes below to the linear parent function, f(x) = x, what is the equation fo the new function?

- Vertically stretch by a factor of 3.
- Flip over the x axis.

A. g(x)=3/x
B. g(x) = 3x-1
C. g(x) = -1/3x
D. g(x) = -3x

2 Answers

6 votes

Answer:

D. g(x) = -3x

Explanation:

User Mikael Jumppanen
by
6.1k points
4 votes

Answer:

D

Explanation:

For a function in the form f(x) = x, we can say:

  • the function f(x) = ax is a vertical stretch if a>1 and compress if 0<a<1
  • the function -f(x) is the original, flipped over x-axis

keeping the 2 rules in mind, we can say that

vertical stretch by a factor of 3 would make it f(x) = 3x

Then

flip over x-axis would make it f(x) = -3x

answer choice D is right

User Sanfly
by
6.0k points